Incidence of recently acquired hepatitis C virus infection among HIV‐infected patients in southern Spain. Issue 5 (26th December 2020) - Gonzalez‐Serna, A; Macias, J; Palacios, R; Gómez‐Ayerbe, C; Tellez, F; Rivero‐Juárez, A; Fernandez, M; Santos, J; Real, LM; Gonzalez‐Domenech, CM; Gomez‐Mateos, J; Pineda, JA; et al.
Abstract : Objectives: Spain is close to HCV microelimination, so rates of recently acquired HCV infection (RAHC) should decrease. Nowadays, men who have sex with men (MSM) carry the highest risk of HCV acquisition. Our aim was to estimate the incidence of and the factors associated with RAHC, together with reinfection rates, among patients sexually infected by HIV. Methods: Primary RAHC infection was diagnosed when anti‐HCV antibody seroconversion was documented. In anti‐HCV positive patients, initially without HCV viraemia, a diagnosis of reinfection was established if plasma HCV RNA was detected. Results: All 350 patients tested negative for anti‐HCV at baseline and had at least one follow‐up visit. Among them, there were 16 RAHC cases from 2016 to 2019. RAHC incidence rates [IR (95% confidence interval, CI)] per 100 person‐years were 3.77 (0.5–12.9) in 2016, 1.85 (0.6–4.3) in 2017, 1.49 (0.4–3.8) in 2018 and 1.98 (0.6–4.5) in 2019. Only previous sexually transmitted infections [incidence rate ratio (IRR) = 18.23, 95% CI: 1.93–172.1; P  = 0.011], male sex (IRR = 8.33, 95% CI: 1.38–54.15; P  = 0.026) and sharing chem‐sex drugs (IRR: 4.93, 95% CI: 1.17–20.76; P  = 0.030), were independently associated with RAHC. Four out of 42 (9.5%) patients became reinfected. Conclusions: The incidence of RAHC among HIV‐infected patients showed a decrease after 2016, although a lower but steady incidence of residual cases still remains. HCV reinfections showed a similar pattern. New infections were associated with sharing chem‐sex drugs among MSM.